Reseña/Review (Duguay, Stefanie, “Personal but not private. Queer women, sexuality and identity modulation on digital platforms”, Ox-ford University Press, ISBN: 9780190076191, 192 págs., 2022) - Santiago Prieto, María (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
Reseña/Review (Duguay, Stefanie, “Personal but not private. Queer women, sexuality and identity modulation on digital platforms”, Ox-ford University Press, ISBN: 9780190076191, 192 págs., 2022)